Balancing Equations and Endurance: Enhancing the Engagement of Grade 10 STE Students in Sports Activities - Mirador, Adrian Jacob F. (Future Science / FSH-PH Publications, 2025)
This action research examined the impact of a mini-sports tournament on the sports participation of Grade 10 Science, Technology, and Engineering (STE) students at Bulacan State University–Laboratory High School. The study aimed to address the decreasing engagement in physical activities among students who face heavy academic workloads. A pre-test and post-test survey measured students’ participation levels before and after the intervention, and the data were analyzed using the Wilcoxon Signed Ranks Test, which yielded a z-score of −4.043 and a p-value of .000, indicating a statistically significant difference below the .05 level. Results showed a notable increase in students’ enthusiasm, teamwork, and participation in sports following the tournament. The activity provided an avenue for relaxation and social interaction, helping students balance their academic responsibilities with physical well-being. The findings demonstrate that structured sports programs can effectively promote engagement and motivation without compromising academic performance. This study highlights the importance of integrating physical education and extracurricular sports into academic settings to foster holistic student development and enhance both physical health and academic productivity among high school learners.